OLDER US ADULTS WITH PERSISTENT OLFACTORY DYSFUNCTION FACE INCREASED MORTALITY. (16th November 2018) - Xu, L; Wroblewski, K; McClintock, M; Pinto, J
Abstract: Introduction Poor olfactory function at a single timepoint is an independent predictor of 5-year mortality. However, olfactory function is labile during aging and it is not known whether its trajectory (temporal pattern) better predicts poor health outcomes. Methods Olfaction was measured using a validated test, along with demographic and health information in a representative sample of US older adults from the National Social Life, Health, and Aging Project (NSHAP) (n=1, 443, 52.4% women, aged 73.5 ± 7.5 years) at baseline and five-year follow-up. Mortality information was collected at ten-year follow-up. Multivariate logistic regression modeled the relationship between olfactory trajectories and mortality, controlling for age, gender, race, physical health, and cognition. Results 9.8% of older adults had persistent olfactory dysfunction (hyposmia or anosmia), 8.1% returned to normal, 12.4% developed new dysfunction, and 69.7% sustained persistent normal olfactory function (normosmia) from baseline to five-year follow-up. Five years later, 16.2% were deceased. Older adults with olfactory dysfunction at a single timepoint were more likely to die within five years (OR=1.63, 95% CI=1.12–2.39, p=0.012). This effect was even stronger among those with persistent dysfunction from baseline to five-year follow-up (OR=2.29, 95% CI=1.42–3.67, p=0.001) when compared to those with persistently normal olfaction. Interestingly, the mortality of those who recovered olfactory function or were newly dysfunctional were not different from persistent normosmics (p>0.05, both). Conclusions The trajectory of olfactory decline is a stronger predictor of mortality than one-time measurement. Longitudinal smell assessment could be clinically useful for identifying high-risk older adults.